Evaluation of medium-term consequences of implementing commercial computerized physician order entry and clinical decision support prescribing systems in two 'early adopter' hospitals. (15th January 2014) - Cresswell, Kathrin M; Bates, David W; Williams, Robin; Morrison, Zoe; Slee, Ann; Coleman, Jamie; Robertson, Ann; Sheikh, Aziz
Abstract: Objective To understand the medium-term consequences of implementing commercially procured computerized physician order entry (CPOE) and clinical decision support (CDS) systems in 'early adopter' hospitals. Materials and methods In-depth, qualitative case study in two hospitals using a CPOE or a CDS system for at least 2 years. Both hospitals had implemented commercially available systems. Hospital A had implemented a CPOE system (with basic decision support), whereas hospital B invested additional resources in a CDS system that facilitated order entry but which was integrated with electronic health records and offered more advanced CDS. We used a combination of documentary analysis of the implementation plans, audiorecorded semistructured interviews with system users, and observations of strategic meetings and systems usage. Results We collected 11 documents, conducted 43 interviews, and conducted a total of 21.5 h of observations. We identified three major themes: (1) impacts on individual users, including greater legibility of prescriptions, but also some accounts of increased workloads; (2) the introduction of perceived new safety risks related to accessibility and usability of hardware and software, with users expressing concerns that some problems such as duplicate prescribing were more likely to occur; and (3) realizing organizational benefits through secondary uses of data. Conclusions We identified little difference in the medium-term consequences of a CPOE and a CDS system. It is important that future studies investigate the medium- and longer-term consequences of CPOE and CDS systems in a wider range of hospitals.